2010
DOI: 10.1159/000316929
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Review: Prenatal Diagnosis of Congenital Megalourethra

Abstract: Megalourethra is a rare congenital anomaly characterized by dilatation of the penile urethra which causes functional obstruction of the lower urinary system. We present a case of congenital megalourethra diagnosed prenatally. Transabdominal sonography revealed a male fetus with bilateral hydroureter, hydronephrosis, dilated bladder and normal amniotic fluid. The fetal penis was enlarged and the penile urethra was dilated with ballooning at the distal end. The urethral meatus was identified. The fetus was deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Since the first case report of prenatal diagnosis of CM in 1989 [7], only a few more cases have been reported [8,9,10,11,12,13,14]. Recently, Amsalem et al [2] published the largest series reported so far with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first case report of prenatal diagnosis of CM in 1989 [7], only a few more cases have been reported [8,9,10,11,12,13,14]. Recently, Amsalem et al [2] published the largest series reported so far with this condition.…”
Section: Discussionmentioning
confidence: 99%
“…A prenatal diagnosis of congenital megalourethra was almost made by the ultrasonographic demonstration of a ballooning of the penis [2,3]. There is only one case report that was prenatally diagnosed by use of both ultrasonography and fetoscopy at first trimester [4].…”
Section: Discussionmentioning
confidence: 99%
“…The most common nongenitourinary organ system abnormalities associated with megalourethra are anal imperforation and anal atresia (Promosonthi and Viseshsindh, 2010), both seen in the index case. In the case described by Wu et al (1995), the finding of a malrotated colon with imperforate anus resembles the index case, but the case mentioned was predominantly a PBS, which the index case was not.…”
Section: Discussionmentioning
confidence: 99%